CD4+CD25+FOXP3+ Regulatory T Cells In Allogeneic Hematopoietic Cell Transplantation - Young-Ho Lee; Muhaimin Rifa'i (Journal of Tropical Life Science, 2011)
CD4+CD25+FOXP3+ regulatory T cells (Treg) require activation through the T cell receptor for function. CD4+CD25+FOXP3+ regulatory T cells are believed to be key players of the immune tolerance network and control the induction and effector phase of the immune system. Although these cells require antigen-specific activation, they are generally able to suppress bystander T cell responses once activated. This raises the possibility that antigen-specific Treg may be useful therapeutically by localizing generalized suppressive activity to tissues expressing select target antigens. Treg can exert a potent suppressive effect on immune effector cells reactive to host antigens and prevent graft versus host disease (GVHD) in allogeneic bone marrow transplantation (BMT). Here, we observed that co-transfer of CD4+CD25+FOXP3+ T cells derived from donor type along with the donor bone marrow cells could control GVHD-like reactions by suppressing effectors cells of host responding to the donor hematopoietic compartment, and resulted in prevention of autoimmunity and rejection. We further demonstrate that CD4+CD25+FOXP3+ regulatory T cells can control immune-based morbidity after allogeneic BMT by suppressing the development of granulocytes cells and increasing the level of B cell expression. Keywords : Bone Marrow Transplantation, Regulatory T cells, CD4+CD25+FOXP3+